Confining sub-nanometer Pt clusters in hollow mesoporous carbon spheres for boosting hydrogen evolution activity - Wan, Xian-Kai (2020)
Electrochemical water splitting is considered as a promising approach to produce clean and sustainable hydrogen fuel. As a new class of nanomaterials with high ratio of surface atoms and tunable composition and electronic structure, metal clusters are promising candidates as catalysts. Here, a new strategy is demonstrated to synthesize active and stable Pt-based electrocatalysts for hydrogen evolution by confining Pt clusters in hollow mesoporous carbon spheres (Pt5 /HMCS). Such a structure would effectively stabilize the Pt clusters during the ligand removal process, leading to remarkable electrocatalytic performance for hydrogen production in both acidic and alkaline solutions. Particularly, the optimal Pt5 /HMCS electrocatalyst exhibits 12 times the mass activity of Pt in commercial Pt/C catalyst with similar Pt loading. This study exemplifies a simple yet effective approach to improve the cost effectiveness of precious-metal-based catalysts with stabilized metal clusters.